1995
DOI: 10.1016/0735-1097(94)00391-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary hypertension in children: Clinical characterization and survival

Abstract: Children with primary pulmonary hypertension have a poor survival expectancy, which does not appear to differ from that in adults with primary pulmonary hypertension. Mortality in childhood primary pulmonary hypertension is also associated with variables that assess right ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 32 publications
5
58
0
1
Order By: Relevance
“…Over the past decade, several studies have highlighted successful clinical strategies in the management of children with severe PAH. 136 This may in part be related to the striking physiologic observation by Barst et al 137 and Sandoval et al, 138 which demonstrated that the acute pulmonary vascular response to vasodilators is more common in younger patients than adults (40% in children vs 20% in adults). These findings support the hypothesis that despite past reports of a higher mortality in children than adult patients if untreated, children with IPAH can do quite well with long-term vasodilator therapy.…”
Section: Childrenmentioning
confidence: 92%
“…Over the past decade, several studies have highlighted successful clinical strategies in the management of children with severe PAH. 136 This may in part be related to the striking physiologic observation by Barst et al 137 and Sandoval et al, 138 which demonstrated that the acute pulmonary vascular response to vasodilators is more common in younger patients than adults (40% in children vs 20% in adults). These findings support the hypothesis that despite past reports of a higher mortality in children than adult patients if untreated, children with IPAH can do quite well with long-term vasodilator therapy.…”
Section: Childrenmentioning
confidence: 92%
“…The prevalence of acute vasoreactivity is higher in children than in adults, allowing a higher proportion of children to be treated effectively with calcium channel blocker therapy [13][14][15]. In children with IPAH, BARST et al [13] showed that 5-yr survival rates improved significantly in 31 acute vasoreactive responders treated with calcium channel blockers compared with 43 nonresponders (p50.0002).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Untreated, median survival from diagnosis is 2.6 years in adults (1) and 10 months in children (2). Therapeutic interventions include prostacyclin, endothelin antagonists, and phosphodiesterase type 5 inhibitors, all of which improve hemodynamics, exercise tolerance, and clinical status (3).…”
mentioning
confidence: 99%